Seroprevalence of Leptospira infection in selected rural and urban areas of Bangladesh by rLipL32 based ELISA (IMC Journal of Medical Science, 2017)
Background and objectives: Leptospirosis is a zoonotic infection with worldwide distribution caused by the Leptospira species and predominant in the tropical and subtropical regions. Information on leptospirosis in Bangladesh is limited. The present study was designed to detect anti-leptospiral antibodies in human serum samples in Bangladeshi population by developing an in-house ELISA using recombinant LipL32 (rLipL32) antigen. The study was conducted from April 2014 to December 2014.Method: Healthy individuals from two rural areas and fever cases from one urban healthcare center were enrolled in the study. Rural health centers were located at Sonargoan and Bajitpur sub-district (Upozilla) of Narayaganj and Kishorganj districts. Sonargoan health center is located 26 km south-east and Bajitpur is located 71 km north-east of Dhaka city. About 1-2 ml of blood was collected with aseptic measure and serum was separated and stored at -200C until used. Anti-leptospiral IgG antibody was determined by recombinant LipL32 (rLipL32) antigen based indirect enzyme linked immunosorbent assay (ELISA). Seropositive cases were further confirmed by commercial Leptospira IgG ELISA.Results: The study included 250 febrile cases and 376 healthy individuals from urban and rural areas, respectively. Out of total 626 study population, anti-LipL32 specific IgG antibody was detected in 70 individuals (11.2%). The rate of positivity of anti-LipL32 antibody among the healthy individuals from rural area was 10.6% while the rate was 12.0% in urban febrile population. The rate of positivity in rural and urban population was not significantly (p>0.05) different. Among the urban population, the rate of seropositivity was 9.1% and 16.4% in 21- 40 yrs and above 40 years age group respectively while the rate was 7.2% and 14.0% in rural population respectively. Out of 70 seropositive cases detected by LipL32 ELISA, 65 (92.9%) were positive by commercial ELISA.Conclusion: The present study has revealed that leptospirosis is prevalent in Bangladesh and should be looked for in febrile and clinically suspected cases. The study has also demonstrated that rLipL32 protein may be used as a candidate antigen for the serodiagnosis of leptospirosis.IMC J Med Sci 2017; 11(2): 50-55